2018
DOI: 10.1021/acsami.8b07393
|View full text |Cite
|
Sign up to set email alerts
|

Breathable and Colorful Cellulose Acetate-Based Nanofibrous Membranes for Directional Moisture Transport

Abstract: Textiles with excellent moisture transport characteristics play key role in regulating comfort of the body, and use of color in textiles helps in developing aesthetically pleasing apparels. Herein, we report an aesthetically pleasing and breathable dual-layer cellulose acetate (CA) based nanofibrous membranes with exceptional directional moisture transport performance. The outer layer was synthesized by subjecting CA nanofibers to hydrolysis and reactive dyeing processes, which converted moderately hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 58 publications
2
77
1
Order By: Relevance
“…The resultant showed that the capillary motion in the porous nanofibers can be further enhanced. Babar et al reported a kind of colorful and breathable dual‐layer cellulose acetate/dyed cellulose acetate nanofiber membrane with directional water transport performance. The developed membrane not only exhibited excellent directional water transport performance but also occupied esthetically pleasing appearance.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant showed that the capillary motion in the porous nanofibers can be further enhanced. Babar et al reported a kind of colorful and breathable dual‐layer cellulose acetate/dyed cellulose acetate nanofiber membrane with directional water transport performance. The developed membrane not only exhibited excellent directional water transport performance but also occupied esthetically pleasing appearance.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] Our previous works have reported the preparation of hydrophobic-to-hydrophilic gradient fabrics that can guide directional water-transport from the hydrophobic to the hydrophilic side. In research literatures, the directional water transport was also termed "one-way water transport," "directional wicking," [33][34][35] or "water diode." In research literatures, the directional water transport was also termed "one-way water transport," "directional wicking," [33][34][35] or "water diode."…”
mentioning
confidence: 99%
“…[31,32] Such a unidirectional water penetration phenomenon was also reported by other researchers. In research literatures, the directional water transport was also termed "one-way water transport," "directional wicking," [33][34][35] or "water diode." [36][37][38][39][40] Almost all the directional water transport membranes have a hydrophobic layer on one side and a hydrophilic layer on the other, a typical feature of Janus membranes.…”
mentioning
confidence: 99%
“…Apart from protective clothing, W&B nanofibrous membranes could also be upgraded to possess directional water transport property, thereby holding great promise for the next generation of quick-dry sportswear (Figure 10a). [128,129] Conventional direction water transport fabrics are capable of transmitting body water and moisture mono-directional, thus the perspiration is pulled away from the skin to the atmosphere rapidly. However, they are typically devoid of effective waterproofness in the inverse direction, resulting in poor protective function.…”
Section: Functional Garmentsmentioning
confidence: 99%